The type series of Poromitra crassiceps (Pisces, Melamphaidae) with lectotype designation - Gon, Ofer; Maclaine, James; Collins, Martin A.; Matcher, Gwynneth; Pogonoski, John J. (Zootaxa, 2023)
The type series of Poromitra crassiceps (Günther, 1878) was thought to include specimens from four localities in the Atlantic, Pacific, and Southern oceans. Comparison of the extant syntypes with the original description revealed that the specimen from the Pacific Ocean was not included in the original type series; one syntype from the Atlantic Ocean was never incorporated into the collection of the Natural History Museum, London, and is considered lost, and another cannot be identified due to its bad condition. The fourth syntype, from the Southern Ocean and in the best condition, is designated lectotype of this species. Molecular analysis of tissue samples collected by us as well as publically available COI sequences showed that only one species, P. crassiceps, is currently known from the Southern Ocean. Specimens from this ocean named P. atlantica (Norman, 1929) in the literature and in collections are probably misidentifications of P. crassiceps. The validity of P. atlantica needs confirmation from fresh material from the type locality.